KEDUDUKAN DAN KEWENANGAN GUBERNUR DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH - Arianti, Ni Luh Putu; Ariani, I G A A (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 03, Mei 2014)
In this paper with titled “The position and authority of the Governor in LocalGovernment Administration” issues that discuss are about how the position of governorin the regional administration and the authority possessed any governor in the regionaladministration. The method which used is normative legal research with statuteapproach and the conceptual approach, while legal materials collection techniquesusing literature study which was the materials collected analyzed qualitatively. Basedon analyzed the result that occur at the moment is that the governor has the position asthe head of the autonomous region as well as the deputy chief administrative area orcentral government, but the authorities of the governor in terms of the legislation ismore likely as the representative of the central government. The conclusion that thegovernor has the position as the head of the autonomous region as well asrepresentatives of the central government as the deputy governor Which was theposition of the central government stipulated in Article 37 of Law no. 32 Year 2004 onRegional Government, while its authority as the representative of the centralgovernment provided for in Article 38 paragraph (1) of Law No. 32 Year 2004 onRegional Government.
Keywords: Position, Authority, Governor, Local Government Administration